Magnetic resonance imaging to evaluate gastrointestinal function - Alyami, J.; Spiller, R. C.; Marciani, L. (Neurogastroenterology and motility, 2015)
Magnetic resonance imaging of gastrointestinal (GI) function has advanced substantially in the last few years. The ability to obtain high resolution images of the undisturbed bowel with tunable tissue contrast and using no ionizing radiation are clear advantages, particularly for children and women of reproductive age. Barriers to diffusion in clinical practice so far include the need to demonstrate clinical value and the burden of data processing. Both difficulties are being addressed and the technique is providing novel insights into both upper and lower GI disorders of function at an ever increasing rate. Magnetic resonance imaging of gastrointestinal (GI) function has advanced substantially in the last few years. This paper reviews some of the more established measurements and some of the other exciting new developments in the MRI assessment of GI volumes, motility and transit.